Crescimento e desenvolvimento neurológico de crianças sem microcefalia ao nascer cujas mães tiveram Zika na gestação - Maia, Ana Maria Peixoto Cabral (2019)
INTRODUCTON: Zika virus (ZIKV) is an emerging flavivirus transmitted by the Aedes aegypti mosquito, its main vector. This virus was first isolated in the year 1947 in the Zika forest of Uganda. Following this discovery, cases were reported in Caribbean regions and the Americas. In October 2015, there was an unexpected increase in the birth of children with microcephaly, which happened initially in Pernambuco and later in other states in the Northeast. After this event, the causal relationship between Zika infection in pregnancy and microcephaly occurrence was confirmed. In addition to congenital microcephaly there is the possibility of babies exposed to Zika being born without microcephaly and presenting neurological changes. Because of this, some children with normal head circumference may not have been diagnosed at birth and have late-onset motor development problems. OBJECTIVE: to evaluate the anthropometric profile and developmental milestones of children born without microcephaly whose mothers had zika during pregnancy, in residents of Fortaleza-Ceará, in 2015 and 2016. METHODS: descriptive cross-sectional study, case series, in which children whose mothers had Zika with laboratory confirmation were evaluated in the years of 2015 and 2016, in the city of Fortaleza. Data were collected from January to May 2018 after approval by the Research Ethics Committee. Initially, a search was performed in the Live Birth Information System (SINASC) to verify the presence of malformations at birth. All infants were then placed on the INTERGROWTH-21st curve to verify absence of microcephaly. For those mothers whose telephone number was registered, the home visit was previously scheduled. A home visit was conducted to interview the mother and the children were evaluated to verify anthropometry and developmental milestones, as recommended by the Ministry of Health through the child's health booklet. During the visit, mothers and children were interviewed and evaluated, respectively, using a semi-structured questionnaire. Data were analyzed using Epinfo software. RESULTS: 30 cases were identified. Of these, 17 children participated in the study. The median age of mothers at birth was 26 years, all were symptomatic and with negative TORCH. Most children were born at term (11/17; 64.7%) and vaginal delivery (10/17; 58.8%). At the time of the home visit, all had age-appropriate head circumference. Regarding the evaluation of the developmental milestones, 15/17 (88.2%) presented at least one delay in the developmental milestones, when considering the age group. CONCLUSION: there are late changes in children's neuropsychomotor development, suggesting the need for specialized medical follow-up.